A new home for the long-snouted seahorse : Hippocampus guttulatus : breeding in captivity to preserve in the wild - Jesus, Filipa Faleiro de, 1981- (2011)
Tese de doutoramento, Biologia (Biologia Marinha e Aquacultura), Universidade de Lisboa, Faculdade de Ciências, 2011